Accelerated Long-Term Hearing Loss Progression After Recovery From Idiopathic Sudden Sensorineural Hearing Loss - Early, Samuel; van der Valk, Jens C.; Frijns, Johan H. M.; Stankovic, Konstantina M. (Frontiers in Neurology, 2021)
Background and Introduction: Idiopathic sudden sensorineural hearing loss (ISSNHL) is characterized by rapid onset, typically unilateral presentation, and variable recovery. This case-control observational study aimed to improve patient counseling by objectively characterizing long-term hearing loss progression following ISSNHL, using sequential audiometry in the largest-to-date cohort of patients with ISSNHL. Methods: Patients diagnosed with ISSNHL at a tertiary referral hospital from 1994 through 2018 with sequential audiometry were studied. Case controls with sensorineural hearing loss (SNHL) were matched by age, sex, baseline hearing status, and frequency of sequential audiometry. Hearing loss progression was quantified using Kaplan–Meier (K–M) analysis to account for variable follow-up duration. A subgroup analysis was performed by age, sex, preexisting comorbidities, ISSNHL-associated symptoms, ISSNHL treatment, and degree of post-ISSNHL hearing recovery. Results: A total of 660 patients were identified with ISSNHL. In patients with post-ISSNHL recovery to good hearing [pure tone average (PTA) <30 dB and word recognition score (WRS) > 70%], median time to progression to non-serviceable (PTA > 50 dB or WRS <50%) SNHL was 16.4 years. In patients with incomplete post-ISSNHL hearing recovery, contralateral ears were also at significantly higher risk of SNHL progression over the following 12-year period. Male sex was associated with increased risk of SNHL progression [odds ratio (OR) 3.45 male vs. female] at 5-year follow up. No other subgroup factors influenced the likelihood of SNHL progression. Discussion and Conclusion: Patients should be counseled on continued risk to long-term hearing after stabilization of hearing post-ISSNHL, with particular emphasis on greater risk to the contralateral ear in those with incomplete ipsilateral recovery.